Physiological cyclic stretch up-regulates angiotensin-converting enzyme 2 expression to reduce proliferation and migration of vascular smooth muscle cells. Issue 6 (15th June 2020) - Song, Jiantao; Qu, Haiyan; Hu, Bo; Bi, Chenglong; Li, Mengmeng; Wang, Lin; Huang, Xiaozhen; Zhang, Mei
Abstract: Angiotensin-converting enzyme 2 (ACE2) is considered as an endogenous negative regulator of renin–angiotensin system (RAS), exerting multiple cardiovascular protective roles. Whether mechanical stretch modulates ACE2 expression remains unknown. The present study aimed at investigating whether ACE2 is involved in physiological stretch (10% elongation, 1 Hz) mediated cellular functions and the underlying mechanism. Cultured human aortic smooth muscle cells (HASMCs) were exposed to 10% stretch for indicated time, and real-time PCR and Western blot analysis showed 10% stretch increased ACE2 expression and activity significantly compared with static conditions and increased Ang-(1-7) level, but decreased Ang II level; Brdu incorporation assay and Scratch test showed that ACE2 was involved in the inhibition of HASMCs proliferation and migration by 10% stretch; the Dual-Luciferase Reporter Assay demonstrated that 10% increased ACE2 promoter activity, but had no effect on ACE2 mRNA stability; kinase inhibition study and Electrophoretic mobility shift assay (EMSA) showed that JNK1/2 and PKCβII pathway, as well as their downstream transcription factors, AP-1 and NF-κB, were involved in 10% stretch induced ACE2 expression. In conclusion, our study indicates ACE2 is a mechanosensitive gene, and may represent a potential therapeutic target for mechanical forces related vascular diseases.